Comparative Genomic Studies of Salmonella Heidelberg Isolated From Chicken- and Turkey-Associated Farm Environmental Samples - Deblais, Loïc; Lorentz, Benjamin; Scaria, Joy; Nagaraja, Kakambi V.; Nisar, Muhammad; Lauer, Dale; Voss, Shauna; Rajashekara, Gireesh (Frontiers in Microbiology, 2018)
Salmonella is one of the leading causes of human foodborne gastroenteritis in the United States. In addition, Salmonella contributes to morbidity and mortality in livestock. The control of Salmonella is an increasing problematic issue in livestock production due to lack of effective control methods and the constant adaptation of Salmonella to new management practices, which is often related to horizontal acquisition of virulence or antibiotic resistance genes. Salmonella enterica serotype Heidelberg is one of the most commonly isolated serotypes in all poultry production systems in North America. Emergence and persistence of multi-drug resistant Salmonella Heidelberg isolates further impact the poultry production and public health. We hypothesized that distinct poultry production environments affect Salmonella genomic content, and by consequence its survival and virulence abilities. This study compared the genomic composition of S. Heidelberg isolated from environmental samples (19 chicken and 12 turkey isolates) of different breeder farms (16 chicken and 8 turkey farms) in the Midwest, United States. Whole genome comparison of 31 genomes using RAST and SEED identified differences in specific sub-systems in isolates between the chicken- and turkey-associated farm environmental samples. Genes associated with the type IV secretion system (n = 12) and conjugative transfer (n = 3) were absent in turkey farm isolates compared to the chicken ones (p-value < 0.01); Further, turkey farm isolates were enriched in prophage proteins (n = 53; p-value < 0.01). Complementary studies using PHASTER showed that prophages were all Caudovirales phages and were more represented in turkey environmental isolates than the chicken isolates. This study corroborates that isolates from distinct farm environment show differences in S. Heidelberg genome content related to horizontal transfer between bacteria or through viral infections. Complementary microbiome studies of these samples would provide critical insights on sources of these variations. Overall, our findings enhance the understanding of Salmonella genome plasticity and may aid in the development of future effective management practices to control Salmonella.